the effect of age , type and duration of infertility on prolactin concentration in the serum of hyperprolactinemic infertile women - Barzanchi, M.T. Ridha.; Mahmmod, suhair N.; AL-Omary, hanan I.S. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: